2013
DOI: 10.2147/opth.s50499
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of a glistening-free single-piece hydrophobic acrylic intraocular lens (enVista)

Abstract: PurposeTo evaluate the safety and effectiveness of a single-piece hydrophobic acrylic intraocular lens (IOL; enVista model MX60; Bausch & Lomb, Rochester, NY, USA) when used to correct aphakia following cataract extraction in adults.MethodsThis was a prospective case series (NCT01230060) conducted in private practices in the US. Eligible subjects were adult patients with age-related cataract amenable to treatment with standard phacoemulsification/extracapsular cataract extraction. With follow-up of 6 months, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…39 It is interesting to note that the enVista is the only foldable IOL that has eyelets, contrary to prior IOLs that were made of polymethylmethacrylate, such as the CZ70BD (Alcon Laboratories Inc, Fort Worth, Tex.). 21,38 The small corneal incision used in our study also yielded stable postoperative refractory error results. In addition, the small incision provides the advantage of operating in a relatively closed system that can prevent intraoperative complications such as transient hypotony and can help surgeons to operate comfortably during fixation with improved globe stability.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…39 It is interesting to note that the enVista is the only foldable IOL that has eyelets, contrary to prior IOLs that were made of polymethylmethacrylate, such as the CZ70BD (Alcon Laboratories Inc, Fort Worth, Tex.). 21,38 The small corneal incision used in our study also yielded stable postoperative refractory error results. In addition, the small incision provides the advantage of operating in a relatively closed system that can prevent intraoperative complications such as transient hypotony and can help surgeons to operate comfortably during fixation with improved globe stability.…”
Section: Discussionsupporting
confidence: 54%
“…The enVista IOL is composed of both an optic and haptics with a hydrophobic acrylic polymer. 21 Its optic is biconvex with a body diameter of 6.0 mm and an overall length of 12.5 mm. It has modified C-loop haptics and eyelets at the optic-haptic junctions (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…84 In this study, a very sharp tip was brought onto the surface of the IOL, and the displacement of the tip into the surface was recorded as a function of force applied. 81 It was found that the AcrySof, Hoya, and Sensar materials indented by 800-1000 nm with an applied force of 60 mN, while the PHS copolymer only indented by 150 nm. From these measurements, and the dimensions of the tip, the surface hardness can be calculated.…”
Section: Physical Properties Of Phs Copolymer Iolsmentioning
confidence: 98%
“…Here, we will focus on one modern IOL polymer that is made of materials combining the best aspects of earlier hydrophobic and hydrophilic polymers, used in the Bausch & Lomb enVista (previously the AVS EXACT) and the Eternity IOL in Japan. This particular material, found to be glistening-free when packaged in 0.9% saline solution, 80,81 is currently the only hydrophobic IOL material with a published composition that contains a substantial hydrophilic component. Figure 9 shows the components of this hydrophobic/hydrophilic hybrid material, which is actually a copolymer of three different monomers PEG-PEA/HEMA/styrene (collectively called the PHS copolymer) and a crosslinker.…”
Section: Properties Of New Hydrophobic Iolsmentioning
confidence: 99%